USULAN PERBAIKAN KUALITAS LAYANAN DENGAN METODE SERVQUAL DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) DI KAFE SG - Hendra Pratama; Ossa Sutaarga; Bunga Rifdah Salsabill (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2026)
Based on weekly coffee sales data from March to May 2025, Café SG experienced a downward sales trend. Total sales declined from 1,612 cups in March to 1,222 cups in May, representing a cumulative decrease of 30.17%. This decline aligns with observations from Google Reviews, where Café SG (rating 4.5) ranks lower than nearby competitors (average rating above 4.7). The SERVQUAL analysis reveals a service quality gap of -2.33, indicating that Café SG’s service performance remains well below customer expectations. The Importance Performance Analysis (IPA) identifies three key priority areas requiring immediate improvement: (1) Staff initiative in offering more comfortable seating, (2) Staff proactiveness in asking about customer satisfaction with their orders, and (3) Assurance of customer safety and comfort. Improvements in these areas are expected to enhance customer satisfaction and help restore a positive sales trend. Keywords: Service Quality, Google Review, SERVQUAL, Importance–Performance Analysis.